Kukkutanda Basti (ALBU-PRO Bio-Enemata) vs. Intravenous Albumin in the Management of Hypoalbuminemia: A Comparative Pilot Clinical Study - Dr Dharmesh Chauhan,; Dr Misbah Rangwala,; Dr Hemant Toshikhane,; Dr Anitha H, (The Bioscan, 2026)
Ayurveda offers a wide spectrum of therapeutic modalities, among which Basti therapy plays a significant role due to its systemic action through rectal administration. Kukkutanda Basti, a formulation derived from egg yolk, has been traditionally used to enhance nutritional status. Considering the high cost, limited efficacy, and adverse reactions associated with intravenous albumin therapy, there is a growing need to explore affordable and safer Ayurvedic alternatives for managing hypoalbuminemia. Aim: To evaluate the pharmaceutical characteristics and clinical efficacy of ALBU-PRO Bio-Enemata (Kukkutanda Basti) and to compare its therapeutic outcomes with standard intravenous albumin supplementation in patients with hypoalbuminemia.